1996
DOI: 10.1111/j.1469-7610.1996.tb01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Twin Children with Unfamiliar Partners: Genotypic and Gender Influences on Cooperation

Abstract: This study applied a social-genetic perspective to examine hypotheses concerning displays of cooperation. The sample included children from 14 monozygotic and 16 dizygotic twin pairs, organized into 30 unfamiliar partnerships. Two puzzle completion sessions were videotaped and evaluated on five dimensions of cooperation. Repeated measures of analysis of variance indicated significantly higher ratings among female than male pairs on Overall Cooperation, Mutuality of Goal and Accommodation. Contrary to expectati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Moreover, monozygotic twins (MZs) may differ from dizygotic twins (DZs) and singleton siblings (hereafter, singletons). Some previous studies have suggested differences in sibling relationships and friendship patterns between MZs and DZs (Segal et al, 1996;Thorpe & Gardner, 2006;Zahn-Waxler et al, 1992). Zahn-Waxler et al (1992) reported that an MZ twin who was cooperative with a co-twin was less empathic toward peers, whereas a DZ twin who was cooperative with a co-twin was more empathic toward peers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, monozygotic twins (MZs) may differ from dizygotic twins (DZs) and singleton siblings (hereafter, singletons). Some previous studies have suggested differences in sibling relationships and friendship patterns between MZs and DZs (Segal et al, 1996;Thorpe & Gardner, 2006;Zahn-Waxler et al, 1992). Zahn-Waxler et al (1992) reported that an MZ twin who was cooperative with a co-twin was less empathic toward peers, whereas a DZ twin who was cooperative with a co-twin was more empathic toward peers.…”
mentioning
confidence: 99%
“…Zahn-Waxler et al (1992) reported that an MZ twin who was cooperative with a co-twin was less empathic toward peers, whereas a DZ twin who was cooperative with a co-twin was more empathic toward peers. Segal et al (1996) reported that MZs are less cooperative when paired with an unknown child than are DZs. Moreover, MZs share more friends than DZs (Thorpe & Gardner, 2006).…”
mentioning
confidence: 99%
“…Studies of behaviors such as inhibition and aggression in twins may help us to understand children's social development (Segal et al, 1996). Greater social closeness and cooperation was found between MZ twins for 11-to 83-year-old twins than DZ twins (Segal & Hershberger, 1999), perhaps as a function of their increased interactions with similar peers (their co-twins).…”
mentioning
confidence: 99%
“…Though the aforementioned studies suggest there is little or no difference in levels of cooperation between men and women, other studies have shown otherwise. For example, when examining cooperation using two puzzle completion exercises, Segal, Connelly, and Topoloski (1996) found that 8-11 year-old femalefemale pairs of children showed higher levels of cooperation than any other pair of children. Another study showed that when using a variation of the Prisoner's Dilemma game imitating corporate managerial decisions, college students paired with simulated female partners responded more cooperatively than when paired with a simulated male partner (Ferguson & Schmitt, 1988).…”
Section: * Ementioning
confidence: 99%